2022
DOI: 10.1111/aas.14045
|View full text |Cite
|
Sign up to set email alerts
|

Surviving sepsis campaign: International guidelines for management of sepsis and septic shock in adults 2021 ‐ endorsement by the Scandinavian society of anaesthesiology and intensive care medicine

Abstract: Sepsis and septic shock remain a leading global cause of mortality and morbidity. [1][2][3] Anaesthesiologists and intensivists are regularly involved in the identification, resuscitation and management of adults with sepsis and septic shock. In November 2021, the Surviving sepsis campaign: international guidelines for management of sepsis and septic shock 2021 was published. 4 The Clinical Practice Committee (CPC) of the Scandinavian Society of Anaesthesiology and Intensive Care Medicine (SSAI) decided to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This concept has also been confirmed from the experimental results. The APACHE-II scoring system is a scoring method for assessing disease severity in critically ill patients [ 19 ]. Patients with severe sepsis may experience abnormal changes in physiological indicators at any time due to organ failure, such as electrolyte imbalance, severe acidosis, arrhythmia, and the APACHE-II score will also change accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has also been confirmed from the experimental results. The APACHE-II scoring system is a scoring method for assessing disease severity in critically ill patients [ 19 ]. Patients with severe sepsis may experience abnormal changes in physiological indicators at any time due to organ failure, such as electrolyte imbalance, severe acidosis, arrhythmia, and the APACHE-II score will also change accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding clinical implication, our study was observational, and focused on ICU patients in which pneumonia was ruled out by chest imaging. Patients with pneumonia or those with sepsis-related organ failure should be treated with antibiotics without delay, as this may impact survival [ 32 ]. Considering the available evidence and the fact that the absence of respiratory sample on ICU day-1 was associated with a lower probability of being weaned from mechanical ventilation in our work, clinicians should make every effort to document and treat bacterial bronchitis, using all available tools (direct analysis of respiratory sample, biomarkers) to ascertain respiratory tract bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis,a severe, potentially fatal, organic dysfunction caused by infections or suspected infections,which has the characteristics of severe disease, rapid progression and low cure rate.Sepsis remains a major cause of morbidity and mortality worldwide, with increased burden in low-and middle-resource settings.The manifestations are various, such as fever, chills, palpitation, shortness of breath, shock,and mental symptoms,and so on.Sepsis can develop into SS [1][2] .As we all know, the application of antibiotics plays a crucial role in the treatment of sepsis.Current guidelines suggest that antibiotics administered within 1 hour of diagnosis can signi cantly improve patient outcomes [3] .According to a 2006 study of 2,731 adults with pyaemia showed that each 1h delay in antibiotic using resulted in a 7.6% increase in mortality.However,Taylor SP [4] et al found that there was no signi cant difference in the mortality of sepsis patients with a recognition delay of less than 6 hours or a drug administration delay of less than 1.5 hours through their study.Therefore, this study investigated the effect of rst-dose antibiotic delay intervals on the clinical e cacy of sepsis patients attending the emergency department. Methods 1.1Patient selection:A total of 452 patients with sepsis were retrospectively selected, which including 257 males and 195 females, from 2020.01 to 2022.12 in our hospital.We chose two diagnostic criteria for sepsis:digital signature of infection or suspected infection;digital signature of Sequential Organ Failure Assessmen,(SOFA), rises ≥ 2 points above the baseline.We de ned SS as persistent hypotension on the basis of sepsis,which need to maintain mean arterial pressure ≥ 8.67kPa or blood lactic acid ≥ 2 mmol/L on the basis of adequate blood volume supplementation with pressure raising drug.We de ned infected patients as those who were prescribed antibiotics within 12 hours of emergency triage and ordered to be used for blood or urine cultures and CRP, PCT, ,blood cells increased [5][6] .The primary outcome we considered in patients with sepsis was the in-hospital fatality rate.Exclusion criteria: Patients who do not meet the diagnosis of sepsis; Patients who with incomplete clinical data.…”
Section: Introductionmentioning
confidence: 99%